Prevalence of Aspergillus fumigatus skin positivity in adults without an apparent/known atopic disease in Uganda. (August 2021) - Kwizera, Richard; Bongomin, Felix; Olum, Ronald; Worodria, William; Bwanga, Freddie; Meya, David B.; Kirenga, Bruce J.; Gore, Robin; Fowler, Stephen J.; Denning, David W.
Background: Skin prick testing (SPT) is an important investigation in the evaluation of allergy to fungal pathogens. However, the background sensitivity to fungal allergens among healthy people in Uganda is unknown. Our aim was to assess the background prevalence of Aspergillus fumigatus SPT positivity in apparently healthy adults without known atopic disease in Uganda. Methods: For this pilot study, we recruited 50 healthy volunteers using convenience sampling, 56% of whom were health workers. We performed the SPT for A. fumigatus according to manufacturer's instructions. A wheal diameter of ⩾3 mm was considered positive. Results: The prevalence of A. fumigatus skin positivity was 60% (30/50). Participants with a positive A. fumigatus SPT were significantly younger than those with a negative result [median age (years): 28 versus 35; p = 0.005]. Conclusion: There is a high skin positivity against A. fumigatus among non-atopic healthy Ugandan adults. There is an urgent need to establish a normal wheal cut-off value for this population. SPT alone may be an unreliable test for the diagnosis of A. fumigatus associated allergic syndromes. More studies are needed to define the prevalence of A. fumigatus skin positivity among non-atopic healthy population in Africa.